Biochemical Benefits, Diagnosis, and Clinical Risks Evaluation of Kratom - Fluyau, Dimy; Revadigar, Neelambika (Frontiers in Psychiatry, 2017)
Background: Kratom (Mitragyna speciosa) is a tropical tree with a long history of traditional use in parts of Africa and Southeast Asia. Kratom is also known as Thom, Thang, and Biak.Its leaves and the teas brewed from them have long been used by people in that region to manage pain and opioid withdrawal and to stave off fatigue.Kratom is actually consumed throughout the world for its stimulant effects and as an opioid substitute(in form of tea, chewed, smoked, or ingested in capsules).Some case reports have associated kratom exposure with psychosis, seizures, intrahepatic cholestasis, other medical conditions and deaths. The clinical manifestations of Kratom are not well-defined and the clinical studies are limited. Data suggest that both stimulant and sedative dose-dependent effects do exist, but a growing concern for the drug’s effects and safety of use has resulted in national and international attention primarily due to an increase in hospital visits and deaths in several countries that are believed to have been caused by extracts of the plant.In this study we aim to use existing literature to clarify both benefits and risks of kratom as well as its diagnosis evaluation as Kratom misuse is an emerging trend in the western world. Methods: Literature review using databases such as Embase, Medline, PubMed, Cochrane Library, and Mendeley from 2007 to 2017 were evaluated by all authors. Results: Kratom suggested benefits are stimulant and sedative effects and antinociceptive effects.Kratom may cause intrahepatic cholestasis, seizure, arrhythmia, impair memory function, and death.Symptoms such as euphoria, feeling relaxed, aggression, hostility, psychosis, polyuria, dry mouth, vomiting and jerky movements are reported.Liquid chromatography/mass spectrometry and ion mobility spectrometry( IMS) seem to be the most promising techniques to screen kratom extracts. Conclusion: Our data analysis has not determined if biochemical benefits of kratom may prove to outweigh its toxicity and risks.Serious toxicity is rare, usually after high dosage. Kratom clinical psychological and medical manifestations can be disturbing. Kratom( Mitragyna speciosa) use, among multiple compounds of the leaf appear to be increasing in the Western World.Methods to accurately identify Kratom compounds are still ongoing.